Survey on Free Trade Agreements and Customs Unions - Carsten Weerth (Global Trade and Customs Journal, 2009)
From 1948 to 1994, the General Agreement on Tariffs and Trade (GATT) Secretariat received 124 indications of Regional Trade Agreements (RTAs) relating to the trade in goods, and since the creation of the World Trade Organization (WTO) in 1995, more than 240 additional RTAs (covering trade in goods and services) have been notified to the WTO. Since 1990, the number of RTAs indicated to the GATT/WTO Secretariat concerning the trade in goods has risen strongly. A World Customs Organization (WCO) survey on the existing Free Trade Agreements (FTAs) and Customs Unions (CUs) in the trade of goods has been published in September 2008. This paper shows the major findings of the WCO survey and puts them into a wider WTO/GATT picture.
Additional information: Pre-Print Data according the the ROMEO/Sherpa-Policy (Yellow Journal).
Keywords: F53; K33; K34; 330; World Customs Organization; World Trade Organization; Regional Trade Agreements; Economic Law; Econmic Integration; Economic Cooperation